The Contribution Of English Women Writers To World Literature - Iusupova, Kandilatkhan (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
English women writers have made a significant contribution to the development of world literature, shaping narrative forms, themes, and literary traditions. From the early works of the eighteenth century to modern and postmodern literature, female authors have explored issues of gender, identity, social class, and morality. This article examines the literary achievements of prominent English women writers such as Jane Austen, Charlotte Brontë, Virginia Woolf, and others, highlighting their influence on both English and global literary canons.